Pengaruh hipnosis lima jari terhadap penurunan kecemasan pasien kanker leher rahim - Adin Mu'afiro, Ova Emilia dan Ira Paramastri (Berita Kedokteran Masyarakat (BKM), 2004)
Background: The incidence of cervical cancer in Indonesia is still the highest among gynecological cancers. Cervical cancer patients generally have anxiety since the uterus has biological and psychological meaning for women. When the anxiety persists and is severe, it can decrease the body immune system. Therefore, an effective way should be sought to decrease anxiety. This study was aimed at examining the role of five-digit hypnosis in reducing anxiety of cervical cancer patient. Methods: The research was a quasi experiment with an equivalent control group design. The subjects of the study were 30 people who were given treatment of five-digit hypnosis and 30 people without treatment. Sample was selected with simple random sampling. The data collection method was questionnaire. The anxiety difference score of the patient was analyzed with pair samples test, while independent samples test was used to examine the influence of five-digit hypnosis with significance level p=0.05. Result and Discussion: The result indicated that there were no significant difference in age, education and length of medication between the two groups (p>0.05). There was a significant anxiety difference